ANALISIS KESULITAN SISWA SMP KELAS VIII DALAM MENGERJAKAN SOAL MATERI BANGUN DATAR - Rina Nur Ubudiyah; Risma Amelia (IKIP Siliwangi, 2021)
This study aims to describe the difficulties of students in solving plane figures questions. This research method is a qualitative method with a case study approach, by describing students with high, medium and low abilities. The subjects of this study were eighth grade junior high school students in West Bandung, taken randomly with 9 students with high abilities who could be said to be good, and students with moderate and low abilities were still classified as low. The instrument used is a test item that refers to indicators of mathematical connection ability. Based on data analysis that students do not understand the questions given, lack of understanding in mathematical concepts, students' mistakes in completing questions based on conceptual and procedural, students feel confused when connecting mathematical material with other material so that they cannot work on the problem. With so the results of the analysis of a sample of junior high school students in West Bandung regency with initial abilities of high, medium, and low level students shows the average level of mathematical ability is still relatively low in students with medium and low abilities.